Co-delivery of Dual Toll-Like Receptor Agonists and Antigen in Poly(Lactic-Co-Glycolic) Acid/Polyethylenimine Cationic Hybrid Nanoparticles Promote Efficient In Vivo Immune Responses - Ebrahimian, Mahboubeh; Hashemi, Maryam; Maleki, Mohsen; Hashemitabar, Gholamreza; Abnous, Khalil; Ramezani, Mohammad; Haghparast, Alireza (Frontiers in Immunology, 2017)
Strategies to design delivery vehicles are critical in modern vaccine-adjuvant development. Nanoparticles (NPs) encapsulating antigen(s) and adjuvant(s) are promising vehicles to deliver antigen(s) and adjuvant(s) to antigen presenting cells (APC), allowing optimal immune responses against a specific pathogen. In this study, we developed a novel adjuvant delivery approach for induction of efficient in vivo immune ‎responses. ‎Polyethylenimine (PEI) was physically conjugated to poly (lactic-co-glycolic) acid (PLGA) to form PLGA/PEI NPs. This complex was encapsulated with R848 (Resiquimod) as TLR7/8 agonist, or MPLA (monophosphoryl lipid A) as TLR4 agonist‎ and co-assembled with cytosine-phosphorothioate-guanine oligodeoxynucleotide (CpG ODN) as TLR9 agonist ‎to form a tripartite formulation (two TLR agonists (inside and outside nanoparticles) and PLGA/PEI NPs as delivery system). The physicochemical characteristics, cytotoxicity and cellular uptake of these synthesized delivery vehicles were investigated. Cellular viability test revealed no pronounced cytotoxicity as well as increased cellular uptake compared to control groups ‎in murine macrophage cells (J774 cell line). ‎In the next step, PLGA (MPLA or R848)/PEI (CpG ODN) were co-delivered with ovalbumin (OVA) ‎encapsulated into PLGA NPs to enhance the induction of immune responses. The immunogenicity properties of these co-delivery formulations were examined in vivo by evaluating ‎the cytokine (IFN-γ, IL-4, and IL-1) secretion and antibody (IgG1, IgG2a) production.‎ Robust and efficient immune responses were achieved after in vivo administration of PLGA (MPLA or R848)/PEI (CpG ODN) co-delivered with OVA encapsulated in PLGA NPs in BALB/c mice. Our results demonstrate a rational design of using dual TLR agonists in a context-dependent manner for efficient nanoparticulate adjuvant-vaccine development.